Prospective Study of Withdrawal of Antiviral Therapy in Patients with Chronic Hepatitis B after Prolonged Virological Response. Issue 11 (6th August 2021) - Gara, Naveen; Tana, Michele M.; Kattapuram, Meera; Auh, Sungyoung; Sullivan, Lauren; Fryzek, Nancy; Walter, Mary; Umarova, Regina; Zhao, Xiongce; Cloherty, Gavin; Doo, Edward; Heller, Theo; et al.
Abstract : Nucleoside analogue (NA) therapy for chronic hepatitis B (CHB) is associated with improved clinical outcomes, but usually requires long‐term use. Whether treatment can be safely withdrawn and the factors associated with post‐withdrawal outcome are not well defined. To assess long‐term outcomes after stopping antiviral therapy, patients with hepatitis B e antigen (HBeAg)–negative CHB who had received antiviral therapy for 4 or more years with hepatitis B virus (HBV) DNA (≤100 IU/mL) were prospectively withdrawn from antiviral therapy and monitored monthly for the initial 6 months and every 3 months thereafter. Those with clinical relapse were retreated according to severity of relapse. Fifteen patients were withdrawn from lamivudine (4), adefovir (5), or a combination of the two (6) after a mean treatment duration of 8.4 years. The mean age was 45 years, 13 were male, and 8 were initially HBeAg‐positive before treatment. After a mean follow‐up of 6.6 years, outcomes differed by pretreatment HBeAg status. All patients who were HBeAg+ before treatment experienced virological relapse (8 of 8); 6 of 8 experienced clinical relapse; 4 of 8 had ALT flares; 5 of 8 required re‐initiation of treatment, one of whom cleared hepatitis B surface antigen (HBsAg); and 3 of 8 remained off treatment, one of whom cleared HBsAg. In contrast, 4 of 7 patients who were HBeAg‐negative before treatment experienced virological relapse, 3 of 7 experienced clinical relapse, and 1 of 7 had an alanine aminotransferase (ALT) flare. None restarted treatment, and 4 of 7 cleared HBsAg. Low pre‐withdrawal HBsAg level was predictive of HBsAg loss. Conclusion : NA therapy can be safely withdrawn with long‐term remission and high rates of HBsAg loss in most HBeAg‐negative patients without cirrhosis. Patients who were initially HBeAg+ should not be withdrawn from treatment, because clinical relapse was frequent and often severe.